Kepasrahan dan Keyakinan Dalam Lagu “Dengan Menyebut Nama Allah” (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Song lyrics are a bridge to convey the message of the creator to the listener as a connoisseur of the song. The songwriter made the song with a specific intention, as well as the song By mentioning the Name of God by Dwiki Darmawan. In this paper the song is interpreted through the semiotic approach of Ferdinand de Saussure. The method used is descriptive, qualitative, interpretive. The result of this study is that the meaning of the lyrics of the song contains an invitation, da'wah to start activities by remembering Allah, so that in the next step reflected resignation and confidence in the heart that the key to happiness is confidence and resignation.